Theology as a Sacrament of Hope - Blume, Margaret (Lumen et Vita, 2015)
In his exegesis of the Transfiguration, Thomas Aquinas says that the vision of divine glory was given to Peter, James, and John in order to prepare them for Christ’s imminent Passion and Resurrection (Cf. Thomas Aquinas, Summa Theologiae III, Q.45). The brilliance of Christ’s face shining like the sun (cf. Mt. 17:2) strengthened the apostles so that they would not lose heart during the darkness that would come, but would wait for Christ’s splendor to be revealed again after the Resurrection. The entire mystery is an icon of hope, for it shows that visions of glory are always given as part of a journey towards their fulfillment. “It is good for us to be here,” Peter recognized, but the apostles were not brought up to the mountain to remain there. The revelation sent them back down the mountain to fare forward in hope. In this paper, I would like to suggest that the work of theology is meant to share in the mystery of the Transfiguration, and thus cultivate the virtue of hope. In this task, theology can learn from literature, for the way of revealing is as important as the message to be revealed. I would like to propose Shakespeare’s The Tempest as a model. In its dramatic structure and wonder-inspiring poetic form, The Tempest participates in the mystery of the Transfiguration, sending the audience away from the strange island refreshed and reoriented, set on the way with Prospero towards freedom. The play challenges theology to present the Good News of the Gospel in a way that makes the glory of the Lord visible by the radiance of its form, and interrupts into ordinary time, like the storm with which The Tempest begins, so that the revelation is not an end in itself. If theology is able to set human beings on a journey by cultivating patience and wonder in the very way it reveals, then it will effect the mysteries that it signifies, and truly impart Christian hope.